ABDULLA AVLONIY’S PLACE IN HISTORY AND HIS SCIENTIFIC LEGACY - Mirhakimova Feruza Xoldorjon qizi,; Vakhobova Gulnoza Avazbek kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation:  This  article  examines  Abdulla  Avloniy,  a  leading  figure  of  the Uzbek  enlightenment  movement  and  one  of  the  most  active  and  influential representatives of the national awakening period, who left a profound mark on  the socio-cultural  life  of  Turkestan.  His  works,  such  as  Birinchi  Muallim  (The  First Teacher), Ikkinchi Muallim (The Second Teacher), and Turkiy Guliston yoxud Axloq (Turkic Garden or Ethics), became key sources in the formation of Uzbek pedagogical thought. Avloniy contributed to the intellectual and moral development of the nation by modernizing the education system, establishing new-method schools, and creating contemporary curricula. His journalistic activity, contributions to the art of theater, and promotion of patriotism and enlightenment played an important role in raising public awareness.